The mechanical response of low to high density Rohacell foams - Poxon, S (2013)
The main aim of this thesis is to generate a deeper understanding of the mechanical behaviour of cellular materials, specifically for their use in aerospace applications. A closed-cell polymer foam material (Rohacell) of various foam densities was chosen for this investigation, and a comprehensive experimental study was conducted which generated significant findings that hitherto have not been reported in the literature. The research presented in this study revealed the following: The quasistatic response of Rohacell foam displays a compression/tension asymmetry in moduli and strength. In-situ experiments revealed that different macroscopic collapse mechanisms at different foam densities drove this behaviour. Improved experimental methods were developed to characterise the material response at various loading rates. Under compressive loading, as the relative density and loading rate increased, a transition in material behaviour from a ductile to brittle response at very high rates (~5x10^3 s^-1) was found, and tests conducted at different temperatures were used to validate and provide a better understanding of the causes for the observed rate dependency. The compression and tension properties of pre-crushed Rohacell foam loaded in different directions were measured, and with the use of three-point-bend tests it was shown that when the foams’ tension/compression asymmetry, or the changes in stiffness and strength due to pre-crushing (i.e. strain-induced anisotropy), are neglected, this leads to incorrect predictions of the foams’ structural response. Finally, a review of some existing Finite Element foam material models was conducted, and their ability to predict the foam response under complex loading was identified. The new data and understanding generated from this thesis will allow engineers and researchers, who are developing constitutive models for predicting the response of foam materials, specifically in aerospace applications, to account for more aspects of the mechanical behaviours in their Finite Element models.